Codonoboea (Gesneriaceae) in Terengganu, Peninsular Malaysia, including three new species - Kiew, Ruth (PhytoKeys, 2019)
Abstract. Of the 92 Codonoboea species that occur in Peninsular Malaysia, 20 are recorded from the state of Terengganu, of which 9 are endemic to Terengganu including three new species, C. norakhirrudiniana Kiew, C. rheophytica Kiew and C. sallehuddiniana C.L.Lim, that are here described and illustrated. A key and checklist to all the Terengganu species are provided. The majority of species grow in lowland rain forest, amongst which C. densifolia and C. rheophytica are rheophytic. Only four grow in montane forest. The flora of Terengganu is still incompletely known, especially in the northern part of the state and in mountainous areas and so, with botanical exploration, more new species can be expected in this speciose genus.